2019
DOI: 10.1002/ange.201908960
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophile Coordination Enabled Regioselectivity in Palladium‐Catalyzed Asymmetric Allylic C−H Alkylation

Abstract: Branched selectivity in asymmetric allylic C−H alkylation is enabled by using 2‐acylimidazoles as nucleophiles in the presence of a chiral phosphoramidite‐palladium catalyst. A wide range of terminal alkenes, including 1,4‐dienes and allylarenes, are nicely tolerated and provide chiral 2‐acylimidazoles in moderate to high yields and with high levels of regio‐, and enantio‐, and E/Z‐selectivities. Mechanistic studies using density‐functional theory calculations suggest a nucleophile‐coordination‐enabled inner‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Given that nucleophile coordination to the π-allylpalladium intermediate facilitates the branch-selectivity (Figure 1e), 20,24 our design plan was initiated with the evaluation of various carbon nucleophiles containing Lewis basic functionalities for the asymmetric allylic C−H alkylation of 1-octene 1 by using Pd 2 (dba) 3 and chiral phosphoramidite L1 as the catalyst, 2,5-dimethylbenzoquinone (2,5-DMBQ) as an oxidant and Na 2 CO 3 as a base (Figure 2a). Although none of glycine Schiff base 2, 2-acylimidazole 3, and α-quinolinylacetamide 4 was able to undergo the desired reaction, to our delight, αbenzothiazylacetamide 5 was reactive enough to participate in the desired reaction and gave the branched product 7 in 78% yield with 24% ee, 12:1 dr and 18:1 b/l.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that nucleophile coordination to the π-allylpalladium intermediate facilitates the branch-selectivity (Figure 1e), 20,24 our design plan was initiated with the evaluation of various carbon nucleophiles containing Lewis basic functionalities for the asymmetric allylic C−H alkylation of 1-octene 1 by using Pd 2 (dba) 3 and chiral phosphoramidite L1 as the catalyst, 2,5-dimethylbenzoquinone (2,5-DMBQ) as an oxidant and Na 2 CO 3 as a base (Figure 2a). Although none of glycine Schiff base 2, 2-acylimidazole 3, and α-quinolinylacetamide 4 was able to undergo the desired reaction, to our delight, αbenzothiazylacetamide 5 was reactive enough to participate in the desired reaction and gave the branched product 7 in 78% yield with 24% ee, 12:1 dr and 18:1 b/l.…”
Section: Resultsmentioning
confidence: 99%
“…21 Although nucleophile coordination to the palladium center impels the reaction to favor an inner-sphere pathway (Figure 1e), allowing for the preferable formation of branched products 22,23 , α-alkene substrates remain restricted to relatively more reactive alkenes, such as allylarenes, 1,4-dienes and others (Figure 1d). 20,[24][25][26][27][28] In sharp contrast, branch-and enantioselective allylic C−H oxidative alkylation of inactivated α-alkenes remains a longstanding formidable challenge and has not been discovered, yet, with the exception of a very few stepwise processes. 29,30 Herein, we report a chiral phosphoramidite-palladium catalyzed branch-and enantioselective allylic C−H alkylation, capable of accommodating almost all types of α-alkenes (Figure 1f).…”
Section: Main Textmentioning
confidence: 99%
“…[17a] Comparing the two competing transition states TS-4 and TS-5 , both were able to provide the branched products via an S N 2'-pathway, but the former showed a more stable but longer vinyl π-allyl-Pd fragment (4.9 Å vs 4.5 Å), therefore, theE/Z -selectivity was conquered by the geometric match of the vinyl π-allyl-Pd fragment, the geometry of the nucleophile and the distortion of Pd-nucleophile bonding. With the use of 2-acylimidazoles or coordinating α-aryl carbonyls as nucleophiles, 1,4-dienes, [36] allyl ethers [37] and N-allylimines [38] all performed well to generate branched products with high levels of regio-and enantioselectivity. Recently, by using α-benzothiazylacetamides and α-heteroaryl ketones as nucleophiles, we established a branch-and enantioselective allylic C-H alkylation capable of accommodating diverse types of α-alkenes, ranging from 1,4-dienes and allylarenes to unactivated α-alkenes tethering a wide scope of appended functionalities.…”
Section: Scheme 9 Correlation Between Regioselection and Ligandmentioning
confidence: 99%
“…Among the landmark advances with transition-metal catalysis, 5,6 palladium (Pd)-catalyzed allylic C-H functionalization of readily available α-alkenes is distinguished by enabling the access to alkene-bearing structurally complex molecules with versatile bond-forming capacity and minimal manipulation of functional groups, [7][8][9] thereby being regarded as an atom-and step-economic alternative to Tsuji-Trost allylation reactions by avoiding the use of preoxidized allylating reagents. 10,11 In recent decades, our group [12][13][14][15][16][17][18][19][20][21][22][23][24] and others [25][26][27][28] have found that trivalent phosphorus ligands are capable of facilitating Pd-catalyzed allylic C-H cleavage through a concerted proton and two-electron transfer process (Scheme 1), 22 thereby generating electrophilic π-allylpalladium intermediates that can be leveraged to forge chemical bonds with a wide range of nucleophiles. 29 Upon using p-quinone as an oxidant, the 16-electron Pd(0) complex 1 bearing a phosphorus ligand, a quinone, and an α-alkene is most likely to be a key intermediate for allylic C-H activation.…”
Section: Introductionmentioning
confidence: 99%